THE IMPACT OF VALUE ENGINEERING TECHNOLOGY ON CUSTOMER RELATIONSHIP QUALITY - Aseel Ali Mezher; Mohammed M.H. A1-Ardhy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The current research aims at highlighting the impact of value engineering technology on the quality of customer relations to a sample of the members of the Board of Directors and the staff in the Quality Department, the Production Department, and the quality department. The marketing department of the Rubber Industries Company/Diwaniya Tire Laboratory in Diwaniya City which has a strength of (100) workers was returned (93) for use and analysis resulting in a response rate (%93). The value Engineering Technology variable has three main dimensions: Preparation for value Research, value Research, and Post-value Research, and the Customer relationship Quality variable has three main dimensions: Trust, satisfaction, and commitment. The research adopted resolution as a basic measurement tool for collecting data that was used to test the main and sub-research hypotheses by using a number of statistical methods, most notably (simple Pearson correlation coefficient, regression analysis, and path analysis) and the results of the current research have proven most of the hypotheses to be valid. The results showed a correlation between value engineering technology and Customer relationship Quality.